Exploring Gender-Based Violence through Critical Discourse Analysis in Drama for Enhancing Literary-Based Learning Perspectives - Ahmad, Mahdi; Sudirman, Sahrun (Actual Insight, 2025)
This study explores gender-based violence through critical discourse analysis of dramatic texts, aiming to enhance literary-based learning. By examining how language constructs and perpetuates GBV within dramatic narratives, the research seeks to deepen understanding of power dynamics, social norms, and the impact of gender-based violence on individuals and society. This study employs a descriptive qualitative method. This study aims to identify the forms of violence experienced by the main female characters in the play A Streetcar Named Desire, as well as the factors behind them. The research data consists of dialogues between characters that reflect the objectives of the study. Data analysis in this research involves three stages: data reduction, data presentation, and drawing conclusions. The findings reveal show that there are three forms of violence depicted by the author in the drama Streetcar Named Desire: physical violence, verbal violence, and sexual violence. All forms of violence are fundamentally rooted in the patriarchal culture that is deeply ingrained in American society, which has shaped social cognition with the view that women are inferior to men. The practical implication exploring gender-based violence through critical discourse analysis in drama can significantly enhance literary-based learning by fostering critical thinking, promoting awareness of social inequalities, and empowering students to challenge harmful norms.